DESAIN APLIKASI TEMPAT BERSEJARAH DI WILAYAH ACEH BERBASIS ANDROID - Zira Darma; Junaidi Salat (Jurnal Sains Riset, 2022)
The historical location for the government is one of the important aspects in increasing tourist visits to become a tourist attraction. However, there are still obstacles faced by the government in terms of developing information, namely the ineffective and efficient information system available for tourists. manuals, such as presenting brochures, pamphlets, and posters for tourists visiting historical sites. This is not effective, even though many advanced technologies are available such as online searches and the use of map websites, but they often have difficulty finding the right place or other facilities in the city. Therefore, the researchers developed an android-based mobile application. By applying this choice of historical locations, tourists can immediately find out favorite historical locations of Aceh and routes or navigation to the location of objects, besides that this application also provides information on various kinds of historical objects in Aceh. With the application of the historical location of Aceh, it is hoped that it will make it easier for the public to obtain information related to the location and information of historical places in Aceh Province.Keywords: historical locations, android, web services, aceh, and tourists.